Vulnerability to the climate cycle and Assessing its effects on vegetation in Saudi Arabia: A Case Study of the Prince's Reserve Mohammed bin Salman Reserve - Alabdali, Abdulla Ahmed (Journal of agricultural, environmental and veterinary sciences, 2024)
The current study seeks to elucidate the impact of climate change and its recurring cycles on nature reserves, with a focus on the Prince Mohammed bin Salman Royal Reserve in Saudi Arabia. The reserve extends along the northwest coast from Duba Governorate in the north to Al-Wajh Governorate in the south, during the period from 2018 to 2024. To achieve accurate results, the study relied on using the latest spatial visualisations of the region, analysing these visualisations using ArcGIS software, and applying target classification to achieve a deeper understanding of the spatial visualisations. In addition, the vegetation index (NDVI) was calculated to determine changes in land cover over time.The study examined changes in vegetation cover and ecological characteristics of the reserve, to identify the main causes of vegetation degradation and study the potential impact of climate change on biodiversity and ecosystems. The study also analysed the reasons that contribute to the development of these reserves as focal points for cities, and the impact of this on improving environmental conditions and contributing to environmental sustainability in light of climate challenges.The research aims to detect changes in the climate cycle and its impact on vegetation cover in the study area, while determining the values and percentage of change in vegetation cover based on Landsat satellite data during the summer season from 2018 to 2024. The study relied on the scientific method and the analytical method in addition to the descriptive method in studying phenomena related to vegetation and climate change.The research includes three main chapters, where the first chapter deals with natural reserves in the Kingdom and reviews the change in the climatic cycle of the Arabian Peninsula region and the factors affecting the reserves. The second chapter analyses the climatic factors specific to the study area, including climatic history, climatic characteristics and climate patterns. The third chapter focuses on the impact of the changing climate cycle on the vegetation in the Prince Mohammed bin Salman Reserve, with a conceptual study for 2018.
Keywords: NDVI; nature reserves; climate cycle